HUBUNGAN KECANDUAN BERMAIN GAME ONLINE PADA SMARTPHONE TERHADAP PRESTASI AKADEMIK SISWA KELAS 12 SMA 1 GERUNG TAHUN 2019 - Sulung Adi Dananjaya; Danang Nur Adiwibawa; Halia Wanadiatri; Dina Qurratu Ainin (Nusantara Hasana Journal, 2022)
World Health Organization (WHO) in 2018 classifies addiction playing online game into the International Classification of Disease11th/ ICD-11). Addicted to playing online games is defined as a pattern ofbehavior gaming or playing ("digital-gaming" or "video-gaming") which has the characteristics, namely the disruption of self-control ability due to playing games. Give priority to games over other activities in daily life; this happens continuously and the intensity increases which causes dependency, sleep disturbance, social disturbance (withdrawal, wasting money) and can reduce academic achievement. This study to determine the relationship of addiction playing online games on smartphones to the academic achievement of class 12th students of SMA 1 Gerung in 2019. This research is observational analytic with design cross sectional. The sampling technique uses purposive sampling. The study was conducted at Gerung 1 High School in December 2010. The research subjects were in class 12th students of sma 1 gerung in 2019 with a total of 252 respondents, then conducted interviews using the Ten-Item Internet Gaming Disorder Test (IGDT-10) questionnaire to determine addictions or not addicted to online games and see the final semester report card grades to determine academic achievement. The data obtained were analyzed by correlation test Spearman Rank. The limit of significance (p) is p ≤ 0.05. The results of the analysis obtained a significance value (p) 0.000 and a correlation coefficient (r) 0.422 which showed a significant relationship between addiction playing online game to achievement in high school students, and the direction of a positive correlation.